2019
DOI: 10.31033/ijrasb.6.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Study of Trace Elements Selenium, Copper, Zinc and Manganese Level in Polycystic Ovary Syndrome (PCOS)

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in premenopausal women, trace elements play an important role in PCOS, selenium performs various biological functions such as defense against oxidative stress, immune function and thyroid function, polycystic ovary syndrome (PCOS) is a common endocrine disorder in premenopausal women, trace Elements have important role in PCOS, selenium is involved in many biological functions, such as, protection against oxidative stress, immune function and thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Therefore, decreased Se level may induce an increased risk factor of cardiovascular disorder, gestational complications, miscarriages, neurodegenerative diseases and increased risk of cancer. Women with PCOS are susceptible to infertility, hirsutism, increased inflammatory factors and increased biomarkers of oxidative stress 22 . Tumor necrosis factor-a (TNF-a), nuclear factor-kappa b (NF-jb), and interleukin-1 (IL-1) are a few examples of inflammatory cytokines that are prevented from being produced and active by selenium, according to numerous research (IL-1 and IL-18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, decreased Se level may induce an increased risk factor of cardiovascular disorder, gestational complications, miscarriages, neurodegenerative diseases and increased risk of cancer. Women with PCOS are susceptible to infertility, hirsutism, increased inflammatory factors and increased biomarkers of oxidative stress 22 . Tumor necrosis factor-a (TNF-a), nuclear factor-kappa b (NF-jb), and interleukin-1 (IL-1) are a few examples of inflammatory cytokines that are prevented from being produced and active by selenium, according to numerous research (IL-1 and IL-18).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a stable balance between the copper-zinc components is responsible for the effectiveness of enzyme function (SOD). Because of enzyme failure, the imbalance in the copper-to-zinc ratio may raise the ratio of dangerous free radicals in the body, which could cause serious harm to cell membranes and walls 22 . In our study, the PCOS group's copper/zinc ratio was noticeably higher than that of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, decreased membrane fluidity of RBC was associated with higher levels of plasma insulin. It is believed that magnesium deficiency can cause oxidative stress [ 19 , 45 ]. Hypomagnesaemia reduces the sensitivity of peripheral tissues to insulin by diminished autophosphorylation of tyrosine kinase, a component of the insulin β subunit of which magnesium is a cofactor [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypomagnesaemia may also be associated with decreased β-cell proliferation, thus affecting insulin production [ 51 , 52 ]. The magnesium content of red blood cells is a very good indicator of short-term magnesium status, and a low level indicates nutritional deficiencies [ 19 ]. In the presented study, the magnesium content in erythrocytes ranged from 34.0–66.8 mg/L and was slightly higher in women with PCOS than in the control group (statistically insignificant), whereas Mhaibes et al [ 49 ] and Swetha et al [ 53 ] observed significantly lower concentrations of this element in the serum of PCOS patients compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation